Indonesia Court Performance in Fulfillment the Substantive Justice to the Victims of Human Trafficking Crimes - Dewantoro, Dewantoro (Bagian Dasar-Dasar Ilmu Hukum & Hukum dan Masyarakat Fakultas Hukum Universitas Diponegoro, 2023)
Indonesia is in a state of emergency for the crime of trafficking in persons. The need for employment has caused many Indonesian workers to become victims of human trafficking. The crime of trafficking in persons is a violation of human rights to human freedom to work according to one's own will and not be forced and tortured in doing work. The district court as the executor of judicial power in the field of general crimes plays a role in enforcing the law and providing justice, one of which is by imposing restitution decisions for victims of human crimes. The technical rules for implementing restitution are important so that substantive justice for victims of trafficking in persons can be recovered materially.